Efficacy and Safety of Oral Itraconazole and Griseofulvin versus Itraconazole Alone in Patients with Tinea Corporis and Cruris Infection: A Comparative Clinical Study - Yagub Salem Saleh; Bassim I. Mohammad; Thamir A. Kubaisi (Mustansiriya Medical Journal)
Background: Dermatophytosis (tinea) is a worldwide prevalent superficial fungal infection limited to the epidermis, mucosa, hair, and nails. Iraq, like many other countries around the world, is facing the emergence of chronic, resistant, and relapsing tinea infections. Aims: The aim of this study is to evaluate the efficacy, safety, and relapse rate of a combination of itraconazole and griseofulvin versus itraconazole alone in the treatment of chronic tinea infections. Patients and Methods: The research was conducted over 14 months. Patients were divided equally into two groups, each with 55 patients. Group I received a combination of itraconazole and griseofulvin, whereas Group II was on itraconazole alone for 8 weeks. For the assessment of the relapse rate, follow-up was for another 2 months. Results: The mean age (±standard deviation) of the total was 31.27 ± 12.08 years. Males were 71 (64.5%) and females were 39 (35.5%). There was no significant difference in their residency. Family history was positive in the majority of patients, 90 (81.8%). After 2 weeks of treatment, a marked cure was achieved by 34 (61.8%) patients in Group I and 21 (38.2%) in Group II. After 8 weeks, the complete cure was 51 (92.8%) in Group I and 38 (69%) in Group II (P < 0.00). The marked cure was 4 (7.2%) in Group I, whereas 17 (31%) in Group II. The relapse rate after 16 weeks was 7 (12.7%) in Group I and 34 (61.8%) in Group II (P < 0.00). Conclusions: We concluded that therapeutic regimens of itraconazole and griseofulvin were effective, safe, and well tolerated, with a low relapse rate.